2021
DOI: 10.1186/s42238-021-00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Processing and extraction methods of medicinal cannabis: a narrative review

Abstract: Introduction As the cannabis industry transitions from a black market to a legal market, product development, and methods of extraction have become a focal point. To date, more than thousands of chemical constituents have been identified from the cannabis plant, all of which possess different chemical properties that require different conditions for preservation during drying and extraction. However, scientific publications that explore these areas for the cannabis plant are currently lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 56 publications
0
51
0
5
Order By: Relevance
“…Cannabis is chemically diverse, with cannabinoids, phenolic compounds, and terpenes being the most important phytochemicals [ 75 ]. Several conventional extraction techniques have been applied to extract phytochemicals from Cannabis using various solvents [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Different conventional extraction methods, including Soxhlet extraction, maceration, and dynamic maceration, have been employed to extract phytochemicals from Cannabis [ 68 , 75 , 76 , 80 , 82 ].…”
Section: Current Techniques For Extraction Of Phytochemicals From ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Cannabis is chemically diverse, with cannabinoids, phenolic compounds, and terpenes being the most important phytochemicals [ 75 ]. Several conventional extraction techniques have been applied to extract phytochemicals from Cannabis using various solvents [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Different conventional extraction methods, including Soxhlet extraction, maceration, and dynamic maceration, have been employed to extract phytochemicals from Cannabis [ 68 , 75 , 76 , 80 , 82 ].…”
Section: Current Techniques For Extraction Of Phytochemicals From ...mentioning
confidence: 99%
“…Several conventional extraction techniques have been applied to extract phytochemicals from Cannabis using various solvents [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. Different conventional extraction methods, including Soxhlet extraction, maceration, and dynamic maceration, have been employed to extract phytochemicals from Cannabis [ 68 , 75 , 76 , 80 , 82 ]. However, studies have also revealed the caveats of using conventional extraction methods, such as the extraction of unwanted substances and degradation of heat-sensitive compounds due to extraction under high temperature [ 84 ].…”
Section: Current Techniques For Extraction Of Phytochemicals From ...mentioning
confidence: 99%
See 3 more Smart Citations